Peak oxygen uptake evaluation in wheelchair basketball players: Continuous or intermittent progressive field test? - Lepretre, P.-M.; Faupin, A.; Borel, B.; Weissland, T. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: A continuous progressive multistage field test (MFT) was validated to assess wheelchair mobility and estimate peak of oxygen uptake (VO2peak) (Vanderthommen et al. 2002). However, intermittent nature of wheelchair basketball game (Sporner et al. 2009) raised the question about continuous or intermittent incremental test to estimate VO2peak (Castagna et al. 2006). In able-body athletes, Buchheit (2008) observed a lesser inter-individual variation of aerobic performance during an intermittent (IFT) compared to continuous incremental exercises. Hence, this study aimed to compare the physiological responses of wheelchair basketball players (WBP) measured during IFT and MFT. Methods: 18 trained WBP (32.0±5.7y, IWBF classification: 2.9±1.1points) performed on two separate days, MFT and IFT in random order. For both test, initial rolling velocity was set at 6 km/h and increased by 0.37 km/h per min or 0.5km/h per 45s for MFT and IFT, respectively. For both tests, VO2peak and peak values of breath frequency (RF), pulmonary ventilation (VEpeak), heart rate at VO2peak (HR@VO2peak) the peak recovery - rest blood lactate values difference (dLact), and the perceived rating exertion (RPE) were measured. Results: Student`s t-test did not show any difference in VO2peak, VEpeak and RF between both tests. IFT was shorter (12,4±2,4 vs. 14,9±5,1min, P<0.05) but induced higher values of FRV and dLact compared to MFT (14.2±1.8 vs. 11.1±1.9km/h and 8.3±4.2 vs. 6.9±3.3mmol/L, P<0.05). However, HR@VO2peak and RPE values were higher during MFT than IFT (166.8±13.8 vs. 172.8±14.0bpm and 13.8±3.5 vs. 15.3±3.8, respectively, P<0.05). Discussion: Buchheit (2008) earlier reported that IFT led to significantly higher peak of lactate values and final velocity than continuous exercise without significant VO2peak. Braking, accelerate and change direction induced by IFT could explain a greater anaerobic solicitation but also the lesser RPE in our subjects compared to MFT. MFT imposed to turn in a single direction and a longer time duration, which could produce discomfort and higher RPE compared to IFT. Finally, rest periods of IFT would delay cardiac adaptation in our population including spinal cord injury WBP (Schmid et al. 1998). IFT could be used for design interval training sessions in order to increase VO2peak in WBP.